EFFORTS TO DEVELOP SOCIAL EMOTIONAL INTELLIGENCE OF STUDENTS IN RUMAH QUR’AN AL-HAFIZH - Ayu Annisah; Mardianto Mardianto (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2023)
Social emotional intelligence is an important component in individual development that positively influences one's social and emotional life. Santri at Rumah Qur'an Al-Hafizh have special needs in developing their social-emotional intelligence to face challenges related to social interaction and emotional regulation in a social environment. This study aims to identify and analyze the efforts that can be made to develop the social emotional intelligence of the santri at Rumah Qur'an Al-Hafizh. This study uses a qualitative approach with descriptive methods where data collection techniques are carried out by in-depth interviews, observation, and document analysis. The results of the study indicate that there are several efforts that can be made for the development of social emotional intelligence of the santri at Rumah Qur'an Al-Hafizh, namely giving attention to the students, introducing students to various emotions and their effects, creating positive behavior in students, strengthening the behavior of students, building good communication with students, providing opportunities for students to carry out activities related to social-emotional intelligence, and establishing cooperation with parents or guardians of students. This research is expected to contribute to increasing understanding of the importance of developing social-emotional intelligence among santri at Rumah Qur'an Al-Hafizh. The findings of this study can be used as a reference for related parties, including educational institutions, teachers and parents, in designing programs and activities that support the development of the social-emotional intelligence of students.